Answer:
Step-by-step explanation:
y intercept
To find the y intercept, make x = 0
2(0) + y = - 6 zero times anything is 0
0 + y = -6
The y intercept is (0,-6)
x intercept
The x intercept happens when y = 0
2x + 0 = -6 zero added to anything = whatever you started with.
2x = - 6 Divide by 2
2x/2 = -6/2 Do the division
x = - 3
The x intercept = (-3,0)
Answer:
-6r+5
Step-by-step explanation:
4.7 as a fraction would be 4 and 7/10 (7 over 10).
Answer:
18
Step-by-step explanation:
note when dividing the denominator and numerators changes position so when it changes it will be 3×6=18